Monolithic patch antenna for dedicated short‐range communications. Issue 2 (1st January 2013) - Leonardi, O.; Pavone, M.; Cadili, T.; Sorbello, G.; Isernia, T.
Abstract : Dedicated short‐range communications (DSRCs) is a novel short‐ to medium‐range wireless protocol designed for automotive use. The DSRC signals are circularly polarised and allocated in the 5.8 GHz band. Described is the development of a monolithic and compact patch antenna with left‐hand circular polarisation intended for the on‐board unit equipment of a DSRC system. The 40×60×2.455 mm fabricated prototype exhibits a circularly‐polarised gain of about 5.52 dBc with a cross‐polar discrimination of about 20 dB.